Inability to empathize following traumatic brain injury - Rodger Wood (Journal of the International Neuropsychological Society, 2008)
This study examines: (a) the impact of traumatic brain injury (TBI) on emotional empathy, (b) the relationship between emotional empathy and neuropsychological ability, and (c) the influence of low emotional empathy on measures of affect. Eighty-nine patients completed the Balanced Emotional Empathy Scale (BEES), a number of neuropsychological tests, some of which were ecologically valid tests of executive ability, plus two measures of affect, the Beck Anxiety Inventory (BAI) and Beck Depression Inventory (BDI). The TBI cohort showed a high frequency (60.7%) of low emotional empathy scores compared to the control group (31%). There was no relationship between injury severity and the ability to empathize, or between emotional empathy and neuropsychological performance. There was no evidence to suggest that low scores on affective measures influenced emotional empathy scores. A high proportion of TBI patients lack the ability to empathize, but the deficit does not appear related to any specific cognitive impairment and cannot be predicted by measures of affect.